Pemberian Senam Kaki Menggunakan Bola Tennis Lebih Efektif Dibandingkan Menggunakan Koran Dalam Meningkatkan Sensitivitas Kaki Pasien DM - Oktapiani, Ni Made Tari; Suardana, I Ketut; Surasta, I Wayan; Erawati, Ni Luh Putu Sri (Jurnal Gema Keperawatan, 2024)
Diabetes Melitus is chronic disease caused by the pancreas not producing enough insulin. Lack of physical exercise for people with Diabetes Melitus can cause  various problems in the feet, namely neuropathy. Peripheral neuropathy is characterized by decreased sensitivity in the legs caused by disruption of peripheral circulation. The purpose of this study is to determine the difference of foot sensitivity in patient with  Diabetes Melitus between combination of diabetic foot gymnastics using newspapers and ROM compared with combination of diabetic foot gymnastics using tennis balls and ROM in the work area of Public Health Centre Karangasem II. This study used Quasi Experiment with Nonequivalent Control group Design with purposive sampling method from 20 respondents. The assessment instrument uses a foot protective sensation score measured using Monofilament. Foot gymnastics was done 3 times a week within 3 weeks. Data were analyzed by Paired t-test and Independent t-test with ɑ = 0,05. The results showed that the average foot sensitivity of type 2 diabetes melitus patients given a combination of foot gymnastics using tennis ball media and ROM before and after the intervention was 14,5 and 15,0 with p value = 0,015 ( ɑ=0,05), in the control group, gymnastics with tennis balls and ROM obtained an average of 15,1 and 17,4 with p value = 0,001 ( ɑ=0,05). The independent test shown p value of 0,023 ( ɑ=0,05).  It concluded that there were significant differences between the control group and the intervention group. It is expected that a combination of foot gymnastics using tennis ball and ROM will be held in health care institutions in handling patients with Diabetes Melitus.